Axiomatic approach in network science - Goh, Jeremy Jia Hao (Nanyang Technological University, 2024)
What makes a node in a graph central? Existing literature offers various metrics to address this question, but many are too contextualised and lack generality. In this project, we take a closer look at current attempts to axiomatize node centrality. We refine existing axioms, adding comprehensive proofs to strengthen their rigour. By integrating these axioms, we develop an enhanced and improved axiomatic framework for characterising node centrality. Our ultimate goal is to lay a solid theoretical foundation for studying node centrality in complex networks.